Synthesis of Zinc Oxide Nanoparticles with Bioflavonoid Rutin: Characterisation, Antioxidant and Antimicrobial Activities and In Vivo Cytotoxic Effects on Artemia Nauplii - Mansab Ali Saleemi; Batoul Alallam; Yoke Keong Yong; Vuanghao Lim (MDPI AG, 2022)
This study aims to synthesise zinc oxide nanoparticles with rutin (ZnO-R NPs) using a green synthesis approach and characterise the nanostructures for diverse biomedical applications. In this study, the optical and chemical properties of synthesised ZnO-R NPs were verified through Fourier transform infrared (FTIR) spectroscopy and ultraviolet-visible (UV-Vis) spectroscopy. The FTIR spectroscopy revealed a symmetric bending vibration peak of 460 cm−1 for ZnO-R NPs, whereas UV-Vis spectroscopy showed a distinct absorption band at 395 nm. Moreover, the oval-shaped morphology of ZnO-R NPs was verified through scanning electron microscopy and transmission electron microscopy. The synthesised nanoformulation revealed a wurtzite structure with a crystallite size of 13.22 nm; however, the zeta potential value was recorded as −8.50 ± 0.46 mV for ZnO-R NPs. According to an antioxidant study, ZnO-R NPs demonstrated lower free-radical scavenging activity than pure rutin. The cytotoxicity study was conducted using a human breast cancer cell line (MCF-7). In vitro analysis verified that ZnO-R NPs exhibited significantly higher anticancer and microbial growth inhibition activities than standard ZnO NPs (ZnO Std NPs) and pure rutin. In addition, ZnO-R NPs revealed a significantly lower IC50 value than the commercial ZnO Std NPs and pure rutin in MCF-7 cells (16.39 ± 6.03 μg/mL, 27 ± 0.91 μg/mL and 350 ± 30.1 μg/mL, respectively) after 48 h. However, synthesised ZnO-R NPs demonstrated no significant toxicity towards Artemia nauplii. These results highlight the synthesis of rutin-mediated ZnO NPs and their possible chemotherapeutic potential.